Influence of SRI Cultivation on Seed Yield and Quality in Short Duration Rice Variety - A. KRISHNA; N.K. BIRADARPATIL; K. MANJAPPA; B.B. CHANNAPPAGOUDAR (Seed Research, 2026)
An investigation to evaluate the Influence of system of rice intensification (SRI) on seed yield, quality in rice was carried out in ES-18 a short duration variety at Agricultural Research Station Gangavati during rabi 2004-05. SRI method of cultivation, application of FYM and RDF significantly increased the growth parameters such as number of tillers, productive tillers, days to 50% flowering, seed yield and seed quality parameters. Under SRI method, the days to 50 per cent flowering and maturity were four to five days earlier, compared to traditional method. Number of tillers per plant (21.79) and productive tillers per plant 19.53 were higher in SRI method. RDF application also significantly contributed to the total number of spikelets and filled spikelet production. SRI method produced significantly higher (2.88 t ha¹) seed yield over traditional method. Seed germination did not differ significantly among methods of cultivation and manures and fertilizer application and vigour index recorded significantly higher values in SRI method.